Gambaran Kemampuan Bahasa Inggris Mahasiswa Fakultas Kedokteran Umi - Mulfa, Zakiyah; Mokhtar, Shulhana; Mukhtar, Amrizal; Amir, Suliati P.; Aisyah, Windy Nurul (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT English is widely considered the language of medicine. However, according to a report by Education First (EF), the healthcare industry has a very low English proficiency index. To determine the English proficiency level and perception of the importance of English among medical students at UMI. This study employed a quantitative descriptive analysis with a cross-sectional research design. Most students considering English as an important factor in their medical education and future career as a doctor. The English proficiency of medical students at UMI is still very low, with no medical student at UMI achieving the minimum standard score of 500, which is generally recognized for the undergraduate level. The average TOEFL score achieved by medical students at UMI is 420, which is categorized as low intermediate level. Although UMI medical students generally have a good/high perception of English, their English language skills are still underdeveloped. Keywords: Perception, Ability, English Language, Medicine  ABSTRAK Sampai saat ini, bahasa Inggris dianggap sebagai bahasa kedokteran. Namun, berdasarkan laporan Education First(EF), menyatakan bahwa industri kesehatan memiliki indeks kecakapan bahasa Inggris yang termasuk kategori kemampuan sangat rendah. Untuk mengetahui kemampuan bahasa Inggris dan persepsi pentingnya bahasa Inggris bagi mahasiswa kedokteran UMI. Penelitian ini menggunakan jenis penelitian analisis deskriptif kuantitatif dengan desain penelitian cross sectional. Sebagian besar mahasiswa menganggap bahasa Inggris merupakan salah satu faktor penting dalam pendidikan kedokteran dan karirnya di masa depan sebagai seorang dokter. Kemampuan bahasa inggris mahasiswa Fakultas Kedokteran UMI masih sangat kurang, dimana tidak ada mahasiswa Fakultas Kedokteran UMI yang memperoleh nilai standar minimal 500 yang diakui secara umum untuk jenjang S1. Rata-rata skor TOEFL yang mampu dicapai mahasiswa Fakultas Kedokteran UMI adalah skor 420, skor tersebut termasuk dalam kategori tingkat menengah bawah (low intermediate). Persepsi mahasiswa Fakultas Kedokteran UMI terhadap bahasa Inggris secara umum sudah cukup baik/tinggi, tetapi kemampuan bahasa Inggris mahasiswa Fakultas Kedokeran UMI masih kurang. Kata Kunci: Persepsi, Kemampuan, Bahasa Inggris, Kedokteran